The Correlation between Vocabulary Mastery, Reading Habits, and The Students' Writing Ability - Erma Yulistiani; Supriyono Supriyono; Andri Wicaksono; Tommy Hastomo (IJLHE: International Journal of Language, Humanities, and Education, 2020)
The method used in this research is the correlational method. The purpose of this study was to determine the relationship between vocabulary mastery and writing ability, the relationship between reading habits and the writing ability, and the relationship between vocabulary mastery and reading habits with writing ability of the students. Data collection techniques in this study were test and non-test techniques as well as data analysis with statistical analysis. The results of this study are: 1) There is a positive and significant relationship between vocabulary mastery and writing ability of the students. The contribution given by mastery of vocabulary to writing ability is 23,329%; 2) There is a positive and significant relationship between reading habits and writing ability of the students. The contribution given by the variable of reading habits to writing ability is 68.724%; 3) There is a positive and significant relationship between vocabulary mastery and reading habits with writing ability of the students. The contribution given is 71.91%. These results provide information that the variables of vocabulary mastery and reading habits have a significant influence on writing ability.